PREDICTING OF BREAST CANCER RISK USING MACHINE LEARNING WITH FEATURE SELECTION THROUGH XGBOOST - Al Azhar, Cahya Mutiara; Pujiono, Pujiono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2025)
Abstract: Breast cancer is the leading cause of death for women globally, exacerbated by late detection. This study proposes a breast cancer risk prediction framework using XGBoost with SelectKBest feature selection. It aims to improve the accuracy and efficiency of early detection through exploratory data analysis, coding, SMOTE to address class imbalance, and feature selection (k=29). As a result, the XGBoost model achieved 98.1% accuracy, 98.1% recall, 98.1% f1-score, and 98.2% precision on test data, highlighting the importance of feature selection. These results are promising in patient prioritization (triage) for further examination, helping medical personnel identify high-risk patients, thus improving resource allocation efficiency. These findings validate SelectKBest and pave the way for the development of a machine learning-based clinical decision support system for breast cancer early detection workflows. This research contributes significantly to the application of machine learning to support early breast cancer detection. Keywords: breast cancer; feature selection; machine learning; risk prediction; XGBOOST. Abstrak: Kanker payudara menjadi penyebab utama kematian wanita global, diperparah deteksi yang terlambat. Penelitian ini mengusulkan kerangka prediksi risiko kanker payudara menggunakan XGBoost dengan seleksi fitur SelectKBest. Tujuannya meningkatkan akurasi dan efisiensi deteksi dini melalui analisis data eksploratif, pengkodean, SMOTE untuk mengatasi ketidakseimbangan kelas, dan seleksi fitur (k=29). Hasilnya, model XGBoost mencapai akurasi 98.1%, recall 98.1%, f1-score 98.1%, dan presisi 98.2% pada data uji, menyoroti pentingnya seleksi fitur. Hasil ini menjanjikan dalam penentuan prioritas pasien (triage) untuk pemeriksaan lebih lanjut, membantu tenaga medis mengidentifikasi pasien berisiko tinggi, sehingga meningkatkan efisiensi alokasi sumber daya. Temuan ini memvalidasi SelectKBest dan membuka jalan bagi pengembangan sistem pendukung keputusan klinis berbasis machine learning untuk alur kerja deteksi dini kanker payudara. Penelitian ini berkontribusi signifikan dalam penerapan machine learning untuk mendukung deteksi dini kanker payudara. Kata kunci: kanker payudara; pembelajaran mesin; prediksi risiko ; seleksi fitur; XGBOOST.